Inhibitory effect of coriander (Coriandrum sativum L.) extract marinades on the formation of polycyclic aromatic hydrocarbons in roasted duck wings - Yajie Yu; Yiqun Cheng; Chong Wang; Suhong Huang; Yang Lei; Ming Huang; Xibin Zhang (Food Science and Human Wellness)
Coriander (Coriandrum sativum L.) is recognized for its antioxidant property, as a kind of natural phenolic-rich ingredient. Polycyclic aromatic hydrocarbons (PAHs) present a class of heat-driven hazards in foods, especially the processed meat. In this study, the effect of coriander root and leaf extract on the formation and inhibition of PAH8 in roasted duck wings was firstly investigated. Coriander root extract (CRE) and coriander leaf extract (CLE) with five concentration groups (200, 400, 600, 800, 1000 mg/L) were prepared respectively to marinate the duck wings. CRE marinade exhibited greater inhibitory effect on PAH8 formation in roasted duck wings that ranged from 65.0 %–87.4 %. The electron spin resonance study indicated a significantly positive correlation between PAH8 and free radical level, suggesting the participation of radicals in PAHs formation. Also, it was speculated that the inhibitory effect on PAH8 was related to the phenolic compounds identified in coriander marinades. CRE made greater inhibitory effect on the formation of PAH8 and could be considered as a kind of natural source to mitigate PAHs in heat-processed meat products.